Differences between Creativity and Gender in Students with High Abilities Attending a School with Total Grouping - Julián Betancourt; María de los Dolores Valadez; Elena Rodríguez-Naveiras; Juan Francisco Flores; África Borges (MDPI AG, 2022)
Background: Creativity is one of the most relevant aspects in students' training. One of the purposes of the present work is to show the lack of differences between boys and girls in creativity; the other is the possibility of improving creativity among high-ability students who received specific training as part of their intra-curricular content in a total grouping program for gifted students. Method: The sample consisted of 42 students from first to third grade (13 females and 29 males) and 58 students from fourth to sixth grade (21 females and 37 males). Creativity was measured with the CREA test for younger students and with the PIC-N for older students. Training was carried out through an Integral Innovation and Creativity Program (PIIC). Results: The results showed no differences between genders, except in one of the graphic creativity scales (Details). There were improvements due to the training in all measures of narrative creativity and in the scale of elaboration of graphic creativity. Conclusions: The main conclusions are the importance of increasing creativity with specific programs and the need to improve interventions in graphic creativity.